Gut commensal microbiota and decreased risk for Enterobacteriaceae bacteriuria and urinary tract infection. Issue 1 (9th November 2020) - Magruder, Matthew; Edusei, Emmanuel; Zhang, Lisa; Albakry, Shady; Satlin, Michael J.; Westblade, Lars F.; Malha, Line; Sze, Christina; Lubetzky, Michelle; Dadhania, Darshana M.; Lee, John R.
ABSTRACT: Urinary tract infection (UTI) is a common complication in kidney transplant recipients and can lead to significant morbidity and mortality. Recent evidence supports a role for the gut as a source for UTIs but little is known about the relationship between gut commensal bacteria and UTI development. We hypothesized that the abundance of gut commensal bacteria is associated with a lower risk of developing bacteriuria and UTIs. We performed gut microbiome profiling using 16S rRNA gene sequencing of the V4-V5 hypervariable region on 510 fecal specimens in 168 kidney transplant recipients. Fifty-one kidney transplant recipients (30%) developed Enterobacteriaceae bacteriuria within the first 6 months after transplantation ( Enterobacteriaceae Bacteriuria Group) and 117 did not (No Enterobacteriaceae Bacteriuria Group). The relative abundances of Faecalibacterium and Romboutsia were significantly higher in the fecal specimens from the No Enterobacteriaceae Bacteriuria Group than those from the Enterobacteriaceae Bacteriuria Group (Adjusted P value<.01). The combined relative abundance of Faecalibacterium and Romboutsia was inversely correlated with the relative abundance of Enterobacteriaceae (r = −0.13, P = .003). In a multivariable Cox Regression, a top tercile cutoff of the combined relative abundance of Faecalibacterium and Romboutsia of ≥13.7% was independently associated with a decreased risk for Enterobacteriaceae bacteriuria (hazard ratio 0.3, P = .02) and Enterobacteriaceae UTI (hazard ratio 0.4, P = .09). In conclusion, we identify bacterial taxa associated with decreased risk for Enterobacteriaceae bacteriuria and Enterobacteriaceae UTI in kidney transplant recipients, which supports future studies on modulating the gut microbiota as a novel treatment for preventing UTIs.